Eugenics for the Doctors: Medicine and Social Control in 1930s Turkey - (:unkn) unknown (OXFORD UNIV PRESS INC, 2011)
This article aims to add a new dimension to the analysis of the relationship between medicine and eugenics via a discussion of the community of Turkish physicians in the period between the two World Wars. It argues that even though the relationship between the two fields has been discussed before in terms of the professional ideology of doctors, the medical community itself has not come under scrutiny by scholars. It is the purpose of this article to show eugenics as the main unifying edifice of that community and argue that eugenics is to be found in the patterns of social reproduction of the doctors as part of the professional middle class in addition to being those who transfer knowledge of medicine. As can be seen in Turkey in the 1930s, the doctors, in their efforts to construct themselves as the pioneers of modern scientific medicine, as well as the new ruling class of the country, used eugenics extensively both as a means of self-identification, and as a way to build a professional class fit to rule the country.
Keywords: eugenics; medicine; Turkish physicians; hygiene; social and professional networks; local medicine